Chemical composition, botanical evaluation and screening of radical scavenging activity of collected pollen by the stingless bees Melipona rufiventris (Uruçu-amarela) - Silva,Tania M.S. (2009)
Stingless bees in Brazil are indigenous and found all over the country. Bee pollen is used for its nutritional value in the human diet. It is made up of natural flower pollen mixed with nectar and bee secretions. In order to evaluate the chemical composition, free radical scavenging activity, and botanical origin, sample of pollen loads from stingless bee, Melipona rufiventris (Uruçu amarela) was studied. The EtOAc extract of pollen of Melipona rufiventris yielded the following compounds: p-hydroxycinnamic acid, dihydroquercetin, isorhamnetin, isorhamnetin3-O-(6"-O-E-p-coumaroyl)-β-D-glucopyranoside, luteolin, and quercetin. This is the first report of the isolation of isorhamnetin3-O-(6"O-E-p-coumaroyl)β-D-glucopyranoside from pollen. The free radicalscavenging activities of different solvent extracts of pollen were determined using DPPH assay. This activity decreases in the order: EtOAc>EtOH>Hexane extract. It appears that the EtOAc extract of the pollen is a good scavenger of active oxygen species. The botanical evaluation of pollen loads showed the composition by two pollen types, with the dominant type (97.3%) being Scopariadulcis (L.) (Scrophulariaceae) and the minor one Senna obtusifolia (L.) Irwin & Barneby (Fabaceae). This suggests a specific foraging behavior in Melipona rufiventris bees, even in an environment with such a rich botanical diversity as the Northeastern Brazil.